Cosmicizing the sacred within the sacrificial cultus: An exegetical and intertextual analysis of the holiness motif in Exo 29:29, 44 - Phillip, Mario N. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2014)
Scripture presents God as one who is constitutively holy, both in His nature and essence. God’s holiness, while it exclusively inheres in His being, He allows persons and things that belongs to Him and are associated with the sacrificial cultus to participate in His holiness. Thus mortal persons and things can be regarded as holy even though not by nature inherently holy. In Exodus Israel as a nation, along with the priesthood and all its appurtenances, were required to be reflectors of His holiness to others. In Exodus holiness is posited not only as a quality possessed by the priesthood, but as something that is transpired to the inanimate aspects of their lives inclusive of their garments and objects within the realm of the sacrificial cultus. Particularly, the garments of the priest became an outward symbol of their consecration and the holiness to which they bore. Moreover, in Exod 29 the hands of the priest were filled with their appointment for service only when in their holy garments using the holy instruments of service. Holiness in this sense becomes something that is cosmicized in those representing God, as well as the things used in ministry to God.